Stroke Lesion Volumes and Outcome Are Not Different in Hemispheric Stroke Side Treated With Intravenous Thrombolysis Based on Magnetic Resonance Imaging Criteria. Issue 4 (April 2015) - Golsari, Amir; Cheng, Bastian; Sobesky, Jan; Schellinger, Peter D.; Fiehler, Jens; Gerloff, Christian; Thomalla, Götz
<x xml:space="preserve">Abstract</x> Background and Purpose— Patients with right hemispheric stroke (RHS) have been reported to have fewer good outcomes after thrombolysis. We aimed at evaluating outcome after stroke thrombolysis with regards to the affected hemisphere controlling for stroke lesion volume as a potential confounder. Methods— We retrospectively analyzed data from a prospective study of patients with acute stroke treated with intravenous tissue-type plasminogen activator, based on magnetic resonance imaging criteria within 6 hours of symptom onset. Neurological deficit was assessed by the National Institutes of Health Stroke Scale. Lesion volume on acute perfusion imaging, diffusion-weighted imaging (DWI) and perfusion imaging/DWI mismatch were measured. Clinical outcome was assessed after 90 days using the modified Rankin Scale, and relation to affected hemisphere was studied by multivariate analysis. Results— Of 173 patients, 55 (32%) presented with RHS, whereas 118 (68%) had left HS. Baseline National Institutes of Health Stroke Scale was lower in RHS (11.7 versus 13.6; P=0.031). There were no differences in DWI lesion volume (11.0 versus 17.8 mL; P=0.519), perfusion imaging lesion volume (98.9 versus 118.3 mL; P=0.395), perfusion imaging/DWI mismatch (60 versus 85.05 mL; P=0.283). Clinical outcome was also comparable for both groups (modified Rankin Scale, 0–1; P=0.327). In multivariate analysis, DWI lesion volume (P<0.001) and age were associated with modified Rankin Scale at day 90, whereas affected hemisphere was not. Conclusions— We did not find differences between RHS and left HS with regards to stroke lesions volumes or outcome after thrombolysis. Previously reported hemisphere-related differences in stroke outcome may partly results from imbalances in stroke lesion volume between RHS and left HS.